Visible-Light-Induced Decarboxylative Iodination of Aromatic Carboxylic Acids - Jiang, Min; Yang, Haijun; Jin, Yunhe; Ou, Lunyu; Fu, Hua (Synlett, 2018)
A convenient, efficient and practical visible-light-induced decarboxylative iodination of aromatic carboxylic acids has been developed, and the corresponding aryl iodides were obtained in good yields. The method shows some advantages including the use of readily available aromatic carboxylic acids as the starting materials, simple and mild conditions, high efficiency, wide substrate scope and tolerance of various functional groups.
Keywords: visible-light; photoredox; aromatic carboxylic acids; decarboxylation; iodination